Diagnosis and treatment of transthyretin‐related amyloidosis cardiomyopathy. Issue 11 (29th July 2020) - Teng, Catherine; Li, Pengyang; Bae, Ju Young; Pan, Su; Dixon, Richard A. F.; Liu, Qi
Abstract: Transthyretin‐related amyloidosis (ATTR) is a subgroup of amyloidosis that results from extracellular misassembled and toxic amyloid deposits affecting multiple organ systems, and cardiac tissues in particular. Because ATTR often presents as heart failure with preserved ejection fraction (HFpEF), it has been largely underdiagnosed. Once considered incurable with a grave prognosis, ATTR cardiomyopathy has seen the development of promising alternatives for diagnosis and treatment, with early diagnosis and treatment of ATTR cardiomyopathy highly beneficial due to its high mortality rate. For instance, diagnosing ATTR cardiomyopathy previously required a cardiac biopsy, but new modalities, such as cardiac magnetic resonance imaging and radionuclide bone scans, show promise in accurately diagnosing ATTR cardiomyopathy. Ongoing research and clinical trials have focused on identifying new treatments which primarily target amyloid fiber formation by inhibiting TTR gene expression, stabilizing the TTR tetramer, preventing oligomer aggregation, or affecting degradation of amyloid fibers. In this review, we describe the advances made in the diagnosis and treatment of ATTR in order to increase awareness of the disease and encourage a lower threshold for ATTR workup. Our review also highlights the need for improving the screening, diagnosis, and treatment guidelines for ATTR cardiomyopathy.